ANALISIS FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KEPUASAN KONSUMEN PADA HOTEL AMANAS DI KOTA AMBON - Herman Surijadi (Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2017)
This study aims to examine the factors that influence consumer satisfaction in Amans hotels in Ambon City. The population studied was hotel guests staying at Hotel Amans Ambon. The sample used in this study was 104 respondents. The results of this study prove that the variables Reability, Responsiveness, Assurance, Emphaty and Tangible together have a positive relationship to consumer satisfaction of Hotel Amans Ambon. All variables studied, found that the most significant is the Tangible variable which is the appearance of physical facilities and infrastructure facilities owned by the Amans Ambon Hotel. Keywords: Reliability, Responsiveness, Assurance, Emphaty, Tangible, Consumer Satisfaction